Fulven-Dimere und -Trimere. Hinweis auf eine [6 + 4]-Cycloaddition von 6,6-Dimethylfulven - Beat Uebersax; Markus Neuenschwander (CHIMIA)
In contrast to earlier assumptions, thermal reaction of simple fulvenes 1a, b, c at 20°C gives Diels-Alder-dimers 2a, b, c in a relatively high yield. Whereas the dimers 2b and 2c equilibrate easily with the corresponding fulvenes at 60 °C, heating of the fulvene-dimer 2a produces an equilibrium 2a ⇄ 3a. After heating of pure 6,6-dimethylfulvene (1c) for several months at 60°C, a trimeric product 6c is isolated with a 35 % yield (60 % with respect to reacted 1c). Formation of 6c may be explained by a thermodynamically controlled [6 + 4]-cycloaddition of 2 molecules of 1c, followed by a 1,5-H-shift as well as by Diels-Alder-reaction of 5c with a third fulvene molecule.